Proteome changes of fibroblasts and endothelial cells upon incubation with human cytomegalovirus subviral Dense Bodies - Inessa Penner; Mario Dejung; Anja Freiwald; Falk Butter; Jia-Xuan Chen; Bodo Plachter (Scientific Data, 2023)
Abstract Human cytomegalovirus (HCMV) is a pathogen of high medical relevance. Subviral Dense Bodies (DB) were developed as a vaccine candidate to ameliorate the severe consequences of HCMV infection. Development of such a candidate vaccine for human application requires detailed knowledge of its interaction with the host. A comprehensive mass spectrometry (MS)- based analysis was performed regarding the changes in the proteome of cell culture cells, exposed to DB.